PENGENDALIAN KUALITAS PRODUK SENG PADA PT.X - Yusnia Sinambela (Universitas Quality, 2021)
Quality is a physical characteristic of a product in terms of meeting customer satisfaction. Paying attention to the importance of the quality of a product produced by a company, efforts are needed to prevent errors in production activities. The aim of this prevention effort is to reduce the number of reject products produced as small as possible so as to reduce the company's losses. PT X is a manufacturing company that produces zinc. In its production activities, defective products are still found. The purpose of this research is to improve the quality of zinc produced so as to reduce the number of defects in the production of PT. X or if it is possible to achieve zero defect. The data collected is product data generated on January 10 to February 10, 2021. From the calculation of the probability of the risk of disability the largest probability is rust defect with a probability value of 0.47, while the smallest probability of disability risk is perforated defect with a probability value of 0.060. Based on the control chart p, it can be seen that the data obtained is not entirely within the control limits that have been determined even many are out of control limits, only 7 (seven) points are within the control limits, so it can be said that the process is out of control. This indicates that there is a high deviation. This states that quality control at PT. X needs a fix. Supervision of workers on the oven plays an important role in avoiding zinc defects. In addition, workers must also be careful in arranging the composition.